Rolf Geyling (1884-1952) Der Architekt zwischen Kriegen und Kontinenten - Scheidl, Inge (2014)
This publication documents the life and work of the architect Rolf Geyling (1884-1952), who was a former student of Otto Wagner and started his career in Vienna and Bucharest before the First World War broke out. During the war Geyling documented his experiences as an officer of the Habsburger Monarchy with photographs and a detailed diary, which he continued during his imprisonment in Siberia. After five years in several camps - most recently in Vladivostok - Geyling fled to Tianjin in China, where he successfully established himself as an architect until the period of Mao Tse-tung and was particularly involved in the development of modern architecture in northern China.